Developing intercultural competence by teaching literature: principles and practice from a case-study in two Algerian universities - Lamia Nemouchi; Michael Byram (Langue(s) & Parole)
This study investigates the use of literary texts for intercultural learning using a Master course of English as a foreign language in Algeria as an empirical example. We first define essential concepts that guided this course - ‘culture’, ‘language-culture nexus’ and ‘intercultural competence’ - before we explain the socio-linguistic and socio-cultural context in Algeria, as it is the foundation of the choice of literary texts. The empirical study was an action research project that took place in two universities. We explain the research methodology and teaching methodology in which lessons were planned on the basis of Byram’s model (1997) of intercultural communicative competence. In the analysis we draw on the existing literature and extracts from the students’ discussions and worksheets to argue for the significance of using literary texts in encouraging ‘aesthetic reading’ leading to empathetic responses that were significant in developing intercultural communicative competence. Finally, we provide recommendations in terms of theory and practice for teachers and syllabus designers who intend to use literary texts for intercultural learning.